Perceptions of persons who wear face coverings are modulated by the perceivers’ attitude - Leder, Johannes; Koßmann, Lisa; Carbon, Claus-Christian (Frontiers in Neuroscience, 2022)
We examined if the effect of facial coverings on person perception is influenced by the perceiver’s attitudes. We used two online experiments in which participants saw the same human target persons repeatedly appearing with and without a specific piece of clothing and had to judge the target persons’ character. In Experiment 1 (N = 101), we investigated how the wearing of a facial mask influences a person’s perception depending on the perceiver’s attitude toward measures against the COVID-19 pandemic. In Experiment 2 (N = 114), we examined the effect of wearing a head cover associated with Arabic culture on a person’s perception depending on the perceiver’s attitude toward Islam. Both studies were preregistered; both found evidence that a person’s perception is a process shaped by the personal attitudes of the perceiver as well as merely the target person’s outward appearance. Integrating previous findings, we demonstrate that facial covers, as well as head covers, operate as cues which are used by the perceivers to infer the target persons’ underlying attitudes. The judgment of the target person is shaped by the perceived attitude toward what the facial covering stereotypically symbolizes.